Micro-credit and group lending: The collateral effect - Lykke Eg Andersen; Osvaldo Nina (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 1998)
Conventional banking practices do not easily accommodate the financial needs of poor persons. Group-lending, on the other hand, has found several advantages in the context of poor borrowers with no collateral to offer. An important advantage is that the bank's losses due to unsuccessful projects are dramatically reduced, because group members cover at least part of those losses. In effect, a kind of collateral has been created in the group even though each individual had no collateral to offer. This paper will analyze the collateral-effect in a model with two types of entrepreneurs (high-risk and low-risk) and a competitive banking system. We show that with individual lending, the typical situation for poor entrepreneurs in developing countries is likely to lead to a separating equilibrium where only high-risk borrowers are served (at a high interest rate). Allowing for group-lending, however, is likely to result in a pooling equilibrium, where all entrepreneurs are served at a considerably lower interest rate. We complement the theoretical analysis by a comparison of the performance of Bolivia's BancoSol, which practices group-lending, with the other private Bolivian banks, which lend on an individual basis.
Keywords: G20; 330; Micro credit; group-lending; collateral; Bolivia; BancoSol; Kredit; Kreditrisiko; Zins; Wohlfahrtsanalyse; Theorie; Bolivien; Soziologie